High-Pressure, High-Temperature Gamma Ray Spectroscopy Measurements in the Oil Field: Data Quality Improvements Using Cerium-Doped Lanthanum Bromide Scintillation Crystal - Mauborgne Marie-Laure; Haranger Fabien; Allioli Françoise; Rakdte R. J.; Sergeyeva Viktoriya (EPJ Web of Conferences)
In the oilfield industry, exploration of the subsurface is essential to answer questions regarding location, type, quantity, and producibility of hydrocarbons. The environment in which these measurements are made can be severe. The instruments must perform at temperatures exceeding 175°C while being exposed to repeated shocks of 100 g or more and at pressures that can exceed 200 MPa. Under these harsh conditions, the tools must deliver accurate and reliable measurements while operating for hundreds of hours. Because drilling rig operation time is very expensive, the measurements must also be acquired as fast as possible. Thallium-doped sodium iodide (NaI:Tl) is still the most commonly used scintillator material today. In the oilfield industry, NaI:Tl was used initially for natural gamma ray detection, gamma ray scattering-based density measurements, and the detection of neutron-induced capture and inelastic gamma rays. In the early 90s, bismuth germinate (BGO) and gadolinium oxyorthosilicate (GSO) were introduced to the oilfield in downhole tools for the detection of natural gamma ray spectra, formation density measurements, and capture gamma ray spectroscopy. The new detector materials were well suited for gamma ray spectroscopy given their high density and average atomic number. However, their spectroscopy performance was not optimal and worsened rapidly with temperature. More recently, cerium-doped lanthanum bromide (LaBr3:Ce) was introduced, enabling step changes to the neutron-induced gamma ray spectroscopy-measurement performance.